Factors predictive of 90‐day mortality after surgical resection for oral cavity cancer: Development of a recursive partitioning analysis for risk stratification. Issue 9 (19th May 2021) - Shinde, Ashwin; Jones, Bernard; Luu, Michael; Li, Richard; Glaser, Scott; Massarelli, Erminia; Freeman, Morganna; Gernon, Thomas; Maghami, Ellie; Kang, Robert; Zumsteg, Zachary; Karam, Sana D.; et al.
Abstract: Background: Factors that influence postoperative mortality (POM) have been identified, but a predictive model to guide clinicians treating oral cavity cancer (OCC) has not been well established. Methods: Patients with OCC undergoing upfront surgical resection were included. Primary outcome was 90‐day POM (90dPOM). Results: 33 845 were identified using the National Cancer Database. Rate of 90dPOM was 3.2%. Predictors of higher 90dPOM include older age, higher comorbidity scores, nonprivate insurance, lower income, treatment in an academic facility, higher T‐ and N‐classification, radical excision, and presence of positive margins. On RPA, two high‐risk (90dPOM > 10%) patient subsets were identified: patients ≥80 years of age with T3‐4 disease and patients <80 years, with any comorbidity and T3‐4, N2‐3 disease. Conclusions: We identified a subset of patients in this cohort who are at high risk for 90dPOM. These patients may warrant additional perioperative and postoperative monitoring in addition to better preoperative assessment and screening.